Association Between Sarcopenic Obesity and Metabolic Syndrome in Adults: A Systematic Review and Meta-Analysis - Khadra, Dima; Itani, Leila; Chebaro, Yomna; Obeid, May; Jaber, Miryam; Ghanem, Reham; Ayton, Agnes; Kreidieh, Dima; E. Masri, Dana; Kimura, Akira; Tannir, Hana; El Ghoch, Marwan (Current Cardiology Reviews, 2020)
Background: In the last two decades, a new phenotype termed Sarcopenic Obesity (SO), in which sarcopenia and obesity coexist, has emerged. Objective: The aim of this systematic review and meta-analysis was first to assess the prevalence of Metabolic syndrome (Mets) among individuals with and without SO, and second, to determine if SO may increase the relative risk of Mets. Methods: This study was conducted in adherence to the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guidelines and the data were collated by means of metaanalysis and narrative synthesis. Results: Twelve studies including a total of 11,308 adults with overweight or obesity of both genders met the inclusion criteria and were reviewed, revealing two main findings. First, a similar overall prevalence of Mets in individuals with SO (61.49%; 95% CI: 52.19-70.40) when compared to those without SO (56.74%; 95% CI: 47.32-65.93) was identified. Second, the presence of SO appears not to increase the risk of Mets with respect to those without SO (RR = 1.08, 95% CI: 0.99- 1.17, p = 0.07). Conclusion: No higher prevalence of Mets among individuals with SO when compared to those with obesity only, nor a significant association between SO and a higher risk of Mets was found.
Keywords: overweight